MANAJEMEN PEMBELAJARAN KITAB KUNING DI MADRASAH TSANAWIYAH NU MIFTAHUL FALAH CENDONO DAWE KUDUS - Muhammad Khafid; Barowi Barowi; Munasir Munasir (Intelegensia : Jurnal Pendidikan Islam, 2019)
Abstract This research is aimed to determine the management of planning, implementation, and learning evaluation.as well as the supporting factors and inhibiting factors of learning yellow book in Islamic Junior High School NU Miftahul Falah Cendono Dawe Kudus. This research use qualitative approach with descriptive qualitative type. The research is located in Islamic Junior High School NU Miftahul Falah Cendono Dawe Kudus. Subject of this research is teachers, head teacher, students, supervisor, and school committee. The technique of collecting data uses observation and in-depth interviewing about the learning management of yellow book. The data obtained is tested for validity by using triangulation. The data is also analyzed use inductive method and deductive method with interactive model by Milles and Huberman which started from data reduction, data presentation, and concluding or verification. From the result of data analysis it can be obtained that: 1) learning management consist of 3 stages, they are planning, implementation, and evaluation and follow-up. 2) Supporting factors of learning are obtained from competent teachers, extra hours to learn yellow book, and availability of references in library. The inhibiting factor is just some students, especially male students who sometimes lack discipline during learning process. Keywords: Islamic School, Yellow book, Learning management